2012
DOI: 10.7771/1932-6246.1143
|View full text |Cite
|
Sign up to set email alerts
|

Insight Problem Solving: A Critical Examination of the Possibility of Formal Theory

Abstract: This paper provides a critical examination of the current state and future possibility of formal cognitive theory for insight problem solving and its associated "aha!" experience. Insight problems are contrasted with move problems, which have been formally defined and studied extensively by cognitive psychologists since the pioneering work of Alan Newell and Herbert Simon. To facilitate our discussion, a number of classical brainteasers are presented along with their solutions and some conclusions derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 83 publications
1
39
0
Order By: Relevance
“…But this does not mean we cannot be systematic and methodical about exploration. As there seems to be the general feeling that problem solving research is stuck (Batchelder and Alexander, 2012;Ohlsson, 2012;van Rooij et al, 2011), perhaps, there is a need for more systematic exploration. Luckily, there are many systematic exploratory methods to be found in applied research that we can build on (e.g., Crandall et al, 2006).…”
Section: Systematic Exploration With Introspective Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…But this does not mean we cannot be systematic and methodical about exploration. As there seems to be the general feeling that problem solving research is stuck (Batchelder and Alexander, 2012;Ohlsson, 2012;van Rooij et al, 2011), perhaps, there is a need for more systematic exploration. Luckily, there are many systematic exploratory methods to be found in applied research that we can build on (e.g., Crandall et al, 2006).…”
Section: Systematic Exploration With Introspective Methodsmentioning
confidence: 99%
“…Luckily, there are many systematic exploratory methods to be found in applied research that we can build on (e.g., Crandall et al, 2006). More concretely, several authors have recently suggested to collect a large set of standardized insight problems and use them to get a better empirical base in order to understand insight problem solving (Batchelder and Alexander, 2012;Chu and MacGregor, 2011). Having standards in terms of problem difficulty and problem similarity will certainly be useful for designing and comparing studies.…”
Section: Systematic Exploration With Introspective Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypothesized causes of this variation in move and insight problems are many and vary from the problem-specific (e.g., Kershaw & Ohlsson. 2004) to the general (Ash & Wiley, 2006;Batchelder & Alexander, 2011;Kaplan & Simon, 1990;Ohlsson, 2011;Öllinger & Knoblich, 2009;Ormerod et al, 2002). …”
Section: Introductionmentioning
confidence: 99%